2013
DOI: 10.1093/jxb/ert093
|View full text |Cite
|
Sign up to set email alerts
|

Zm908p11, encoded by a short open reading frame (sORF) gene, functions in pollen tube growth as a profilin ligand in maize

Abstract: Double fertilization of flowering plants depends on the targeted transportation of sperm to the embryo sac by the pollen tube. Currently, little is known about the underlying molecular mechanisms that regulate pollen germination and pollen tube growth in maize (Zea mays). Here, a maize pollen-predominant gene Zm908, with several putative short open reading frames (sORFs), was isolated and characterized. The longest ORF of Zm908 encodes a small protein of 97 amino acids. This was designated as Zm908p11 and is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
1
26
0
2
Order By: Relevance
“…The first SEP was discovered in a plant in 1996, a 10 AA peptide expressed from ENOD40 transcript . This was soon followed by more identifications in plants including 36 aa peptide encoded from the POLARIS gene ( Arabidopsis thaliana ), ROTUNDIFOLIA4, Brick, Zm401, and Zm908p11 …”
Section: Introductionmentioning
confidence: 99%
“…The first SEP was discovered in a plant in 1996, a 10 AA peptide expressed from ENOD40 transcript . This was soon followed by more identifications in plants including 36 aa peptide encoded from the POLARIS gene ( Arabidopsis thaliana ), ROTUNDIFOLIA4, Brick, Zm401, and Zm908p11 …”
Section: Introductionmentioning
confidence: 99%
“…Unlike classical peptide hormones and neuropeptides, which are translated as larger precursor proteins followed by limited proteolytic processing (Holst, 2007, Steiner, 1998), these s(m)ORF-encoded polypeptides (SEPs) are short peptides encoded directly from s(m)ORFs (Galindo et al, 2007, Kondo et al, 2010, Magny et al, 2013, Pauli et al, 2014). A small number of well-studied SEPs have indicated that these polypeptides may act as important regulators in many fundamental biological processes, such as metabolism (Dong et al, 2013), development (Kondo et al, 2010, Pauli et al, 2014), and cell death (Hashimoto et al, 2001), but little is known about the biological activities, regulation, or even total number of SEPs. Therefore, discovery and functional characterization of SEPs will expand our knowledge of the composition of the genome and proteome, and provide fundamental insights into the molecular biology of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, six functionally characterized plant sPEPs encoded by transcripts not encoding longer proteins have been reported in the literature, namely, POLARIS (PLS; 36 amino acids), EARLY NODULIN GENE 40 (ENOD40;12,13,24, or 27 amino acids), ROTUNDIFOLIA FOUR (ROT4; 53 amino acids), KISS OF DEATH (KOD; 25 amino acids), BRICK1 (BRK1; 84 amino acids), Zm-908p11 (97 amino acids), and Zm-401p10 (89 amino acids) Dong et al, 2013;Crappé et al, 2013;Andrews and Rothnagel, 2014). However, based on the TAIR10 annotation of the Arabidopsis genome, 131 functionally annotated peptides (<100 amino acids) without an NSS can be identified.…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%